2018
DOI: 10.1002/cae.22075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emotional analysis on the improvement of experimental e‐learning systems

Abstract: E‐learning, also known as online learning or technology enhanced learning, needs to provide more heterogeneous learning including not only Web‐based courses and virtual classrooms but also remote labs with an affective recognition system. These latter allow students to interact with real experiments conducted from a distance with real‐time facial expression recognition using a webcam. However, multiple systems do not include this kind of learning. Thus, students' motivation, interest, and learning might be neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…This ITS is able to monitor the evolution of the learning process as the student interacts with the system. In another study, Khalfallah and Slama (2018) built an ITS called LabTutor for engineering students. LabTutor served as an experienced instructor in enabling students to access and perform experiments on laboratory equipment while adapting to the profile of each student.…”
Section: Intelligent Tutoring Systemmentioning
confidence: 99%
“…This ITS is able to monitor the evolution of the learning process as the student interacts with the system. In another study, Khalfallah and Slama (2018) built an ITS called LabTutor for engineering students. LabTutor served as an experienced instructor in enabling students to access and perform experiments on laboratory equipment while adapting to the profile of each student.…”
Section: Intelligent Tutoring Systemmentioning
confidence: 99%
“…in courses or in lab sessions [63,68]. In discussing artificial intelligence implementations, Khalfallah and Slama [37] mention an intelligent tutoring system called "LabTutor," which they adapted to the online profile of every student to serve as an experienced teacher for students who access and perform experiments on real laboratory equipment. Through F I G U R E 4 Geographical presentation of engineering through distance education publications technology-enhanced learning or distance learning practices, students can have the opportunity to collaborate in virtual communities.…”
Section: Text Mining and Social Network Analysismentioning
confidence: 99%
“…Similarly, the fully online engineering courses could use a combination of virtual or remote laboratories, residential schools, on-campus modules, workplace experience, and simulation software [59]. The study conducted by Khalfallah and Slama [37] revealed that a majority of students realized that remote practical work can be extremely useful for engineering students.…”
Section: Text Mining and Social Network Analysismentioning
confidence: 99%
“…"Emotions are basic psychological systems regulating an individual's adaptation to personal and environmental demands. Emotions are closely related to cognitive, behavioral, motivational and physiological processes; therefore they are generally important for learning and achievement" (Seel, 2012;Khalfallah and Slama, 2018). An influential research on human behaviour put forward that the learning process is more effective when it is associated with positive relations than it is with building negative one.…”
Section: Emotionsmentioning
confidence: 99%